2021
DOI: 10.15587/1729-4061.2021.242986
|View full text |Cite
|
Sign up to set email alerts
|

Development of prediction model of steel fiber-reinforced concrete compressive strength using random forest algorithm combined with hyperparameter tuning and k-fold cross-validation

Abstract: Because of the incorporation of discontinuous fibers, steel fiber-reinforced concrete (SFRC) outperforms regular concrete. However, due to its complexity and limited available data, the development of SFRC strength prediction techniques is still in its infancy when compared to that of standard concrete. In this paper, the compressive strength of steel fiber-reinforced concrete was predicted from different variables using the Random forest model. Case studies of 133 samples were used for this aim. To design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…As the simplest ML technique, MLR was implemented to predict the CS of SFRC and showed R 2 of 0.888, RMSE of 6.301, and MAE of 5.317. Al-Abdaly et al 50 reported that MLR algorithm (with R 2 = 0.64, RMSE = 8.68, MAE = 5.66) performed poorly in predicting the CS behavior of SFRC. Khademi et al 51 used MLR to predict the CS of NC and found that it cannot be considered an accurate model (with R 2 = 0.518).…”
Section: Resultsmentioning
confidence: 99%
“…As the simplest ML technique, MLR was implemented to predict the CS of SFRC and showed R 2 of 0.888, RMSE of 6.301, and MAE of 5.317. Al-Abdaly et al 50 reported that MLR algorithm (with R 2 = 0.64, RMSE = 8.68, MAE = 5.66) performed poorly in predicting the CS behavior of SFRC. Khademi et al 51 used MLR to predict the CS of NC and found that it cannot be considered an accurate model (with R 2 = 0.518).…”
Section: Resultsmentioning
confidence: 99%
“…We built the best hyper parameter search by sckit learn's grid search function with cross-validation. Because every ML model had its own set of hyper-parameters, the overall search for each model was unique ( Al-Abdaly et al, 2021 ). When selecting hyper-parameters, it is important to keep in mind that performance is a primary factor in determining which parameters to use.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a hyperparameter optimization process is required. (21,22) There are no established standards or methods for selecting hyperparameters in machine learning. It is common to find the hyperparameter that minimizes the error by changing it according to the actual data of machine learning.…”
Section: Predictive Evaluation Using Machine Learning Techniquesmentioning
confidence: 99%
“…It is common to find the hyperparameter that minimizes the error by changing it according to the actual data of machine learning. (21) The optimal hyperparameter can be derived through various trial and error tests. Therefore, in our work, a k-fold cross validation method was used.…”
Section: Predictive Evaluation Using Machine Learning Techniquesmentioning
confidence: 99%